2004
DOI: 10.1097/00005176-200408000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol for Constipation in Children Younger Than Eighteen Months Old

Abstract: Oral powdered polyethylene glycol at a maintenance dose of 0.78 g/kg/day is safe and effective for patients younger than 18 months. Dose and safety profiles are similar for those reported in older children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 9 publications
4
35
0
3
Order By: Relevance
“…Both milk of magnesia and polyethylene glycol 3350 without electrolytes were efficient and safe in our infants and toddlers. The safety and efficiency of polyethylene glycol in children <18 months of age was also reported recently by Michail et al 14 It has been reported that cow's milk protein intolerance is a cause of constipation in young children. 15 Intolerance to cow's milk protein occurs in 0.3% to 7.5% of otherwise healthy infants.…”
Section: Discussionsupporting
confidence: 71%
“…Both milk of magnesia and polyethylene glycol 3350 without electrolytes were efficient and safe in our infants and toddlers. The safety and efficiency of polyethylene glycol in children <18 months of age was also reported recently by Michail et al 14 It has been reported that cow's milk protein intolerance is a cause of constipation in young children. 15 Intolerance to cow's milk protein occurs in 0.3% to 7.5% of otherwise healthy infants.…”
Section: Discussionsupporting
confidence: 71%
“…Constipation secondary to morphine was observed in 40.9% of patients in the first week, in 38.8% in the second week and in 16.6% in the third week. In spite of the small number of patients, these results may be considered similar to the international literature 17,18 and are attributed, in addition to the drugs, to the fact that the study was prospective and that specific attention was given to constipation. It is worth reminding that, according to the literature, constipation secondary to morphine affects 70% to 80% of terminal patients and is difficult to contro l7, 13,14,19 .…”
Section: Discussionsupporting
confidence: 82%
“…Mais recentemente, o polietilenoglicol (PEG) vem sendo citado como opção terapêutica [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] na CICF em pediatria.…”
Section: Introductionunclassified